Students’ Mathematical Literacy Ability in Terms of Self Efficacy Through Problem Based Learning with PMRI Approach (Unnes Journal of Mathematics Education, 2023)
This research aims to (1) find out whether mathematical literacy through Problem-Based Learning with PMRI Approach (PBL-PMRI) achieves Actual Completion Limit (ACL); (2) find out whether mathematical literacy through PBL-PMRI is classically complete; (3) to find out whether the average and proportion of mathematical literacy through PBL-PMRI is more than the average and proportion of mathematical literacy through PBL; (4) knowing whether students' self-efficacy influences mathematical literacy through PBL-PMRI; (5) describe mathematical literacy through PBL-PMRI based on students' self-efficacy. The research method used is a mixed method with a sequential explanatory design. Sampling in this research with cluster random sampling. While taking the subject with purposive sampling. The results of this research are: (1) mathematical literacy through PBL learning with the PMRI approach achieves Actual Completion Limit (ACL); (2) mathematical literacy through PBL-PMRI learning achieves classical mastery; (3) the average and proportion of students' mathematical literacy through PBL-PMRI are more than the average and proportion of mathematical literacy through PBL; (4) self-efficacy affects mathematical literacy through PBL-PMRI; (5) description of students' mathematical literacy with categories: (a) self-efficacy on fulfilling the four indicators; (b) self-efficacy is in the moderate of fulfilling 3 indicators and tends not to fulfill 1 indicator; (c) lower self-efficacy tends to fulfill 2 indicators, tends not to fulfill 1 indicator, and does not fulfill 1 indicator.